A Study of Poppies in October by Sylvia Plath from the Lens of Critical Discourse Analysis - Siddiq, Sadaf; Shakil, Ezzah; Batool, Maria (Annals of Human and Social Sciences, 2024)
This paper intends to scrutinise the chosen poem i.e. Poppies in Octoberby keeping in view the basic postulates of CDA. The purpose of CDA is to highlight the power relations at work in the text. The analytical framework of the study is situated within the footsteps of Fairclough’s Three Dimensional Model of Critical Discourse Analysis (1995).The study comprises of qualitative analysis and involves the description, interpretation and explanation of the discursive structures within the text of the poem.The discussion section of the poem reveals the underlying meaning of the poem which is about the dichotomy between life and death and the oppression of women in an unappreciative patriarchal world. The brief poem by Plath is laden with meaning. The textual, discursive and social practices in the poem reveal a lot about the gruesomely violentand melancholic tone of the poem. The study recommends incorporating such analyses in ESL classrooms because it can foster a holistic approach to language learning by combining linguistic proficiency with cultural understanding and critical thinking skills.